Modal Budaya dan Mobiliti Sosial Pekebun Kecil Getah di Alor Gajah, Melaka: Cultural Capital and Social Mobility of Smallholder Rubber Farmers in Alor Gajah Melaka - Abdullah, Azlina; Amdan, Atekah (GEOGRAFI, 2017)
The community development in society especially in terms of social mobility is influenced by the economic capital, social capital and cultural capital. This article discusses about the cultural capital owned by smallholder rubber farmers and the level of inter-generational social mobility. The survey was conducted on 50 RISDA smallholder rubber farmer in Alor Gajah, Melaka. The sample was selected using purposive sampling method. The research findings shown that cultural capital are assets and can be utilized by smallholder rubber farmers in their economic activities. The level of cultural capital is high with a mean score of 4.08 to 4.44. Whereas the level of social mobility which measured based on socio-economic status, the findings shown that smallholder rubber farmers experienced upward or vertical social mobility. Finally, a community could enjoy the well-being of life when individuals believe that they can and have the equal opportunity to improve their quality of life and the skills, efforts and talents will be enjoyed by their children as well.